The transformation and upgrade of China's manufacturing industry in Industry 4.0 era. (8th June 2020) - Sun, Yu; Li, Ling; Shi, Hui; Chong, Dazhi
Abstract: Currently, many countries are striving to transform and upgrade their manufacturing industries. Manufacturing development strategies such as Industry 4.0 have attracted a lot of attention from both industry and academia. To provide a fundamental basis and reference for the development of China's manufacturing industry, this study reviews the key concept and implementation mechanism of Industry 4.0. After analysing main problems existing in China's manufacturing industry, this study provides a key strategy for the transformation and upgrade of China's manufacturing industry. A digital manufacturing ecosystem framework is also proposed to explore theoretical and practical significance of this strategy.